ASPEK HUMOR DALAM RETORIKA DAKWAH GUS BAHA DI MEDIA YOUTUBE - Sadili, Imam (Jurnal Dakwah Tabligh, 2022)
Humor in da’wa rhetoric is an important component, so that speech is lively and liked by many people, especially layman audiences. This article aims to formulate Gus Baha’s view about humor and its urgency in da’wa rhetoric as well as the humor classification in several of Gus Baha’s speeches on the youtube channel. The study uses the qualitative method, by describing the data obtained from observation of Gus Baha’s speech on several youtube channels and some related books and research. Results of the study found that Gus Baha saws humor as worship, a sign of pious (ālim), and a refreshing instrument for a mukmin. The study also classifies Gus Baha’s humor into 3 types; Sufi humor, Islamic boarding school (pesantren) humor, and fiqh humor.